2018
DOI: 10.1097/ceh.0000000000000219
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Multisource Feedback in Assessing Medical Performance: A Systematic Review

Abstract: Evidence for the validity of MSF has, across a number of domains, been well established. However, the size and quality of the existing evidence remains variable. To determine the extent to which MSF is considered a valid instrument to assess medical performance, future research is required to determine the following: (1) how best to design and deliver MSF assessments that address the identified limitations of existing tools and (2) how to ensure that involvement within MSF supports positive changes in practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…A further strength of the study is that we described not only the internal structure but also the response process and consequences in detail, thus addressing a gap in the literature. A recent review on the validity of MSF summarized that these aspects were reported too seldom, and as a result, knowledge on these was still limited [51].…”
Section: Discussionmentioning
confidence: 99%
“…A further strength of the study is that we described not only the internal structure but also the response process and consequences in detail, thus addressing a gap in the literature. A recent review on the validity of MSF summarized that these aspects were reported too seldom, and as a result, knowledge on these was still limited [51].…”
Section: Discussionmentioning
confidence: 99%
“…It is important as well that feedback collected by means of MSF is given to the assessed doctor in a facilitated fashion, either by an appraiser, mentor, facilitator, or coach. This, as well as the quality of this facilitation, has been suggested to have a role in the physicians' acceptance and subsequent behavioral change by a review of effectiveness of multi-source feedback [45].…”
Section: Patient Questionnairementioning
confidence: 99%
“…9 10 12 19 One method of assessment called 360° feedback or multisource feedback (MSF), requires evaluations that are completed by multiple people in a person's sphere of influence. 20 Literature examining MSF assessment in Canadian residents has left the CanMEDS role of Leader underexplored. Around the world, efforts to develop an MSF tool to assess leadership have not specifically assessed the Leader role, have failed to seek feedback from patients or have done neither.…”
Section: Original Researchmentioning
confidence: 99%
“…Around the world, efforts to develop an MSF tool to assess leadership have not specifically assessed the Leader role, have failed to seek feedback from patients or have done neither. [20][21][22][23][24] Our research question was, 'What does the construct of leadership look like in junior residents using an MSF tool in a healthcare setting?' The purpose of this study was to describe the construct of leadership in junior resident physicians by implementing a new MSF survey tool called the Learning by Evaluation from All-inclusive 360 Degree Engagement of Residents (LEADER) tool.…”
Section: Original Researchmentioning
confidence: 99%